2018
DOI: 10.15244/pjoes/80867
|View full text |Cite
|
Sign up to set email alerts
|

Production of Cellulases by Bacillus cellulosilyticus Using Lignocellulosic Material

Abstract: Cellulases are the most useful enzymes in industry. They can be produced by fungi, bacteria, or actinomycetes. The high cost of cellulases is mainly due to the substrates used in production, and also the slow growth rate of fungi. Most of the research on cellulase production has focused on fungi, with relatively lesser stress on bacteria [1]. Bacteria, which have high growth rates compared to fungi, have good potential to be used in cellulase production [2]. Also, bacteria, owing to their diversity and rapid g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 40 publications
2
2
0
Order By: Relevance
“…However, the enzyme activity shown by this isolate was found to be poor when compared to the other isolates under the study. The data are comparable to the findings reported by Maryam et al [32] on Bacillus cellulosilyticus which showed optimum cellulase production at pH 5 using alkali pretreated substrate as a source of carbon. Nandimath et al [33] isolated Bacillus and Pseudomonas species having cellulolytic potential.…”
Section: Optimization Of Cellulase Productionsupporting
confidence: 89%
“…However, the enzyme activity shown by this isolate was found to be poor when compared to the other isolates under the study. The data are comparable to the findings reported by Maryam et al [32] on Bacillus cellulosilyticus which showed optimum cellulase production at pH 5 using alkali pretreated substrate as a source of carbon. Nandimath et al [33] isolated Bacillus and Pseudomonas species having cellulolytic potential.…”
Section: Optimization Of Cellulase Productionsupporting
confidence: 89%
“…Our results indicated that isolates from the Terfez rhizosphere and those from thermal waters performed best with a CMCase activity of 0.7 to 2.2 U/mL. These results should be compared with those of Maryam et al [27], who indicated that the CMCasic activity is 1.99 U/mL for B. cellulosillyticus and lower by 0.07 U/mL for B. subtilis AS3 [28]. However, other strains of Bacillus are capable of having a higher endoglucanase activity, from 7.3 U/mL to 9.1 U/mL [29].…”
Section: Discussionsupporting
confidence: 53%
“…The concentration of total sugars varied relatively in the same way for all the strains, and it varied from 335 µg/mL to 450 µg/mL; these monomeric sugars are produced from the hydrolysis of the substrate (CMC), which reflects that this substrate is highly digestible by the strains tested. The estimate of the total sugar content in a culture supernatant on medium containing lignocellulosic materials from a strain of B. cellulosilyticus is 179.84 mg/mL [27].…”
Section: Discussionmentioning
confidence: 99%
“…This study is of its kind to report the cellulase producing bacteria from saw dust which is a by product of wood working areas. Furthermore, using 16S rRNA confirmed that one of the isolates is B. stratosphericus, which is for the first time Studies reported that temperature greatly affect growth of microbes and ultimately extra cellular enzyme production [21,22]. Keeping in view, different conditions based on variation in temperature range was provided to the selected strains.…”
Section: Discussionmentioning
confidence: 64%